(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
May, 29, 2023, the newly elected president of Nigeria announced the removal of petroleum subsidy. This announcement led to general increment in prices of goods and services across the country. The impact of the fuel subsidy removal was felt by all institutions including religious institutions which are mostly affected. This paper assess the impact of subsidy removal on Christian’s religious institutions in Nigeria. Secondary data were used. The data were collected from print and online publications. The paper concluded that impact of subsidy removal on Christian’s religious institutions in Nigeria include; increment in operational cost of conducting services, increment in cost of evangelism, reduction in number of worshiper in services, reduction in invitation of external guest speakers, reduction in number of conference attendants, reduction in Christian’s religious institutions income and suspension of projects and programme. Based on this impact identified, the paper recommended that government at every levels should include Christian’s religious institutions in the sharing of their palliative programmes